ANALYSIS EMPIRIS PIL (PHYSICS, I’M IN LOVE) SEBAGAI MODUL BELAJAR FISIKA DI SMP/MTs - Juita, Ani Sri; Nasir, Muhammad; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research was to empirically analyze PIL (Physics, I’m in Love) as a physics learning module at junior high school. This research type using Research and Development (R&D) method in stage of a limited scale product trial. The subject of this research is the eighth grade students in SMPN 5 Pekanbaru. The data of this research is a module assessment score which is given to 37 respondents through a questionnaire. The respondents consisted of 13 mens and 24 womens as users. Furthermore, the data were analyzed for validity test through product moment correlation technique and reliability test through cronbach’s alpha technique using microsoft excel and SPSS program. The result of data analysis obtained the assessment score validity which is given respondents to the module PIL is greater than r table (> 0,325) based on the validity of each item, each indicator, and gender. While the reliability value of modul PIL is greater than 0,7 thas is 0,827. It can be concluded that the empirical analysis based on result data and discussion module PIL is valid and reliable at display, pedagogy, content and technical indicators. In addition to valid and reliable indicators, the module PIL is also declared valid and reliable based on gender. So that module PIL (Physics, I’m in Love) can be used as a physics learning module at junior high school.Key Words: Empirical Analysis, Module PIL, Validity test, Reliability test